THE AVERAGE MEAN OF MARRIAGES THAT END IN DIVORCE - Reuben Soto, Sergio (2013)
This is the final report made from research done on Costa Rica’s divorced couples. The study’s principal aim was to know for how many years were the couples married before their divorce and to calculate its mean. The research enabled us with the ages each couple had when they got married and divorced. Here, we were able to perceive three patterns in the lives of married couples: 1. A period of unsteadiness from their 5th to 23rd anniversary; 2. A period of stability running from the 23rd to the 25th anniversary; 3. A period of instability after 35 years of marriage.